Leflunomide-Induced Hidradenitis Suppurativa - Achraf Machan; Hasna Azendour; Hamza Toufik; Lahsen Achemlal; Mohammed Boui; Naoufal Hjira (Case Reports in Rheumatology)
Hidradenitis suppurativa is an inflammatory disease of the pilosebaceous unit with a chronic intermittent course and a devastating effect on quality of life. Rare reports of drug-induced hidradenitis suppurativa exist. We report on 2 women on follow-up for rheumatoid arthritis, who presented hidradenitis suppurativa after different periods of treatment with leflunomide and who improved few weeks after discontinuation of the medication.